Combined Vacuum Evaporation and Solution Process for High‐Efficiency Large‐Area Perovskite Solar Cells with Exceptional Reproducibility. Issue 13 (17th February 2023) - Tan, Liguo; Zhou, Junjie; Zhao, Xing; Wang, Siyang; Li, Minghao; Jiang, Chaofan; Li, Hang; Zhang, Yu; Ye, Yiran; Tress, Wolfgang; Ding, Liming; Grätzel, Michael; et al.
Abstract: Organic–inorganic hybrid perovskites exhibit outstanding performances in perovskite solar cells (PSCs). However, the complex solution chemistry of perovskites precursors renders it difficult to prepare large‐area devices in a reproducible way, which is a prerequisite for the technology to make an impact beyond lab scale. Vacuum processing, instead, is an established technology for large‐scale coating of thin films. However, with respect to the hybrid perovskites it is highly challenging due to the high vapor pressure of the organic ammonium halide. In this work, vacuum evaporation of lead iodide and solution processing of organic ammonium halide is combined to produce large‐area homogeneous perovskite films with large grains in a highly reproducible way. The resulting PSCs achieve a power conversion efficiency (PCE) of 24.3% (certified 23.9%) on small area (0.10 cm 2 ), 24.0% (certified 23.7%) on large area (1 cm 2 ) and 20.0% for minimodule (16 cm 2 ), and maintain 90% of its initial efficiency after 1000 h 1‐sun operation. The vacuum evaporation prevents advert environmental effects on lead halide formation and guarantees a reproducible fabrication of high‐quality large‐area perovskite films, which opens a promising way for large‐scale fabrication of perovskite optoelectronics. Abstract : Vacuum evaporation of lead iodide and solution processing of organic ammonium halide are combined to produce large‐area homogeneous perovskite films with high reproducibility. The resulting PSCs achieve a power conversion efficiency (PCE) of 24.0% (certified PCE 23.7%) on large area (1 cm 2 ) under AM 1.5G illumination, which is currently the highest PCE for large area perovskite photovoltaics.